2011
DOI: 10.3899/jrheum.110377
|View full text |Cite
|
Sign up to set email alerts
|

Synovial and Peripheral Blood CD4+FoxP3+ T Cells in Spondyloarthritis

Abstract: Our data show accumulation of Foxp3+ T cells within inflamed joints. These Foxp3+ T cells are mainly of stable T regulatory phenotype. The high frequency of Foxp3+ T cells in pSpA might contribute to the spontaneous resolution and remitting course of arthritis in pSpA as compared to the more persistent joint inflammation in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The increased percentages of the Tregs population in our AS patients suggest that an enhanced immuno-regulatory mechanism is present in disease processing. This may result from the existence of a positive feedback system in which the inducible regulatory T cells are generated and triggered due to ongoing inflammation [27,30,31]. It has been shown that the FoxP3 expression can be induced in human CD4 + CD25 − T cells after cell activation [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…The increased percentages of the Tregs population in our AS patients suggest that an enhanced immuno-regulatory mechanism is present in disease processing. This may result from the existence of a positive feedback system in which the inducible regulatory T cells are generated and triggered due to ongoing inflammation [27,30,31]. It has been shown that the FoxP3 expression can be induced in human CD4 + CD25 − T cells after cell activation [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…DNA extraction and methylation‐specific real‐time PCR were performed as in Appel et al 2011 and Wieczorek et al, 2009 , using a minimum of 60 ng bisulfite‐treated (EpiTect; Qiagen) genomic DNA. Results are reported as % T cells with demethylated TSDR region.…”
Section: Methodsmentioning
confidence: 99%
“…Regulatory T cells (Tregs) are a subset of CD4+ CD25high T lymphocytes that require forkhead box transcription factor (FOXP3) for their suppressive function [4, 8, 9]. Tregs derived from the thymus mediate suppression through a contact-dependent mechanism including cytotoxic T-lymphocyte antigen 4 (CTLA-4) [10].…”
Section: Introductionmentioning
confidence: 99%